The impact of p53 mutation on tumor immune evasion: mechanistic insights and clinical implications - Liang, Luo; Wang, Weidong (Frontiers in Immunology, 2026)
Mutant p53(Mtp53) not only loses its canonical tumor-suppressive functions but also acquires oncogenic gain-of-function properties, positioning it as a central orchestrator in reshaping the tumor immune microenvironment. This review systematically delineates how Mtp53 actively establishes and sustains an immunosuppressive niche through multiple interconnected mechanisms, including chronic inflammation, immune cell dysfunction, reprogramming of cancer-associated fibroblasts, metabolic dysregulation, epigenetic hijacking, and potentially aberrant liquid–liquid phase separation, thereby promoting immune evasion and therapeutic resistance. We integrate current evidence to propose a conceptual “metabolism–epigenetics–immunity” axis: Mtp53-driven metabolic reprogramming—such as accumulation of lactate or α-ketoglutarate—can modulate chromatin modifications and immune gene expression. Notably, the full in vivo causal chain of this axis remains unestablished; existing support derives primarily from stepwise experimental data and strong correlations. The immunological impact of Mtp53 is highly context-dependent, shaped by co-mutations and tissue origin. In TP53/KRAS co-mutant non-small cell lung cancer (NSCLC), Mtp53 enhances tumor immunogenicity and improves response to immune checkpoint inhibitors (ICIs); conversely, in immunologically “cold” tumors—such as triple-negative breast cancer, pancreatic ductal adenocarcinoma, and colorectal cancer—it promotes T-cell exhaustion or myeloid suppression, reflecting marked cancer-type heterogeneity. Therapeutic approaches include Mtp53 reactivators (e.g., APR-246, PC14586), degraders, synthetic lethal strategies, and neoantigen vaccines. Although APR-246 showed efficacy in a phase II trial (NCT03072043), it failed to improve survival in phase III (NCT03745716) due to lack of TP53 mutation stratification. Its combination with pembrolizumab (NCT04383938) demonstrated acceptable safety (immune-related adverse events in ∼12%) but limited efficacy, underscoring the need for biomarker-guided, precision-based combinations. Thus, a multidimensional biomarker platform is urgently needed—one integrating TP53 mutation subtypes (e.g., R175H vs. nonsense mutations), dynamic ctDNA monitoring (VAF ≥ 0.01%), tumor immune microenvironment (TIME) features (e.g., TILs, MDSCs), and spatial multi-omics—to enable precise molecular stratification and personalized intervention in Mtp53-driven cancers.